PENGEMBANGAN PERANGKAT PEMBELAJARAN MODEL KOOPERATIF - SHELLA WARDYA RELANDINA (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2014)
The development of one stay two stray learning package on vertebrate topic has been conducted. This study aimes to produce learning package using cooperative learning model with One Stay Two Stray type which is feasible and describe the theoretical and empirical feasibilities of the package. This research was done using the 4-D model. However, it was done for the first three stages. The results show that the lesson plan gets 3,71 of score, and the Student Worksheet gets 3,83. Lesson plan implementation get the score of 3,87. In addition, student’s activities were different for every meeting, and there was no irrelevant activity. Score of spiritual competence was 3,6 and social competence was 3,5. The mastery of knowledge competence was 100%. All of the students gave positive responses to the lesson that used One Stay Two Stray type of cooperative learning model. Based on all of the results, it can be concluded that the learning package is feasible theoretically and empirically. Keywords: Learning package, cooperative learning model with One Stay Two Stray, vertebrates